PENGARUH KUALITAS PENDIDIKAN, CITRA, DAN KEPERCAYAAN TERHADAP KEPUASAN ORANG TUA MURID SDIT (SEKOLAH DASAR ISLAM TERPADU) MIFTAHUL ULUM CINERE - Indah Edityawati, Mega; Subhan (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
The purpose of this study is to determine and analyze the Influence of Education Quality, Image, and Trust on Parental Satisfaction at SDIT Miftahul Ulum Cinere, Depok. The research design employed is explanatory research with data collection through questionnaires. The data analysis model utilized is multiple linear regression. Sample selection was conducted through purposive sampling, yielding a total of 85 respondents for the multiple linear regression analysis. The regression analysis results indicate that 74.3% of the factors influencing parental satisfaction can be explained by education quality, school image, and trust, while the remainder is attributed to other unexamined factors in this study. The F-test results show that collectively, education quality, image, and trust significantly and positively affect parental satisfaction at SDIT Miftahul Ulum Cinere, with an observed F-value of 81.811, which is greater than the critical F-value of 2.710. The t-tests demonstrate that education quality (t = 2.721), school image (t = 2.981), and trust (t = 4.578) individually have significant positive effects on satisfaction, surpassing the critical t-value of 1.663. Trust emerges as the most dominant variable influencing parental satisfaction at SDIT Miftahul Ulum Cinere.